Smartphone addiction and associated risk factors amongst undergraduate medical students in a medical college of Assam: a cross-sectional study - Phukan, Ishan; Chetia, Angchuman; Mahanta, Baidurjya (International Journal Of Community Medicine And Public Health, 2022)
Background: Use of smartphones is becoming increasingly indispensable in today’s world but increased usage creates addiction to it, which is associated with profound social and psychological disturbances. As such, this study was conducted to estimate the prevalence of smartphone addiction amongst undergraduate medical students and to assess their smartphone usage pattern. Methods: This was a cross-sectional study conducted among 304 medical students. A pre-designed, pre-tested structured questionnaire containing the short-version of the smart phone addiction scale (SAS-SV) was used for data collection. Data is presented in percentages and association was tested using Chi-square and Fischer’s exact test. Results: Prevalence of smartphone addiction was found to be 44.07%. The most personally relevant smart phone function reported was social-media usage followed by watching videos followed by phone calls. Students using smartphones on an average of 3-4 hours/day and >5 hours/day are 3.2 and 5.7 times more likely to be addicted to smartphones compared to the students’ using smartphones on an average of 11-60 mins/day [95% CI: 1.13-9.29, p=0.02 (3-4 hours/day) and 95% CI: 1.92-16.92, p=0.00 (>5 hours/day)]. Students using smartphones on a frequency of 21-50 times/day and >50 times/day are 6.7 times and 10.9 times more likely to be addicted to smartphones compared to the students’ using smartphones on a frequency of <5 times/day respectively [95% CI: 1.8-24.87, p=0.00 (21-50 times/day) and 95% CI: 2.79-43.1, p=0.00 (>50 times/day)]. Conclusions: Prevalence of smartphone addiction was quite high amongst the medical students compared to previous studies. As such, awareness regarding this upcoming problem amongst students is of utmost importance.